Antioxidant potential of curcuma xanthorrhiza -based serum stick / Mumtazatul Mahfuzah Mahadzir, Nor Azira Irma Muhammad and Nur Afiqah Yusri - Mahadzir, Mumtazatul Mahfuzah; Muhammad, Nor Azira Irma; Yusri, Nur Afiqah (Penerbit UiTM (UiTM Press), 2025)
Solid skincare products are sustainable and convenient alternatives to traditional liquid or semi-solid formulations. Incorporation of natural active ingredients like Curcuma xanthorrhiza (C.xanthorrhiza) extract into solid skincare products can offer potential benefits for skin health. This study investigated the Soxhlet extraction of C. xanthorrhiza using ethanol solvents. The mean total yield was 8.16%. Then, the extract exhibited a promising IC50 value of 20.86 ppm, indicating significant antioxidant activity. Total phenolic content (TPC) was 45.71±0.36 mg GAE/g, and the total flavonoid content (TFC) was 30.06±0.41 mgQE/g thus suggesting the presence of potentially beneficial bioactive compounds. This study was to formulate a novel serum stick formulation that incorporated C. xanthorrhiza extract. The sticks developed have maintained a slightly acidic pH of 5.018 which aligns with healthy skin's natural pH and remains stable. These findings showed that C. xanthorrhiza extract could potentially be developed as a solid skin care product. This research lays the groundwork for further development of C. xanthorrhiza extract-based topical products with potential antioxidant properties. Future studies could explore the efficacy and safety of the formulated serum stick in clinical trials.